PENYEBARAN TEKNOLOGI KONSERVASI LAHAN KERING MELALUI PEMUKA PENDAPAT DI KABUPATEN BANTUL PROPINSI DAERAH ISTIMEWA YOGYAKARTA (THE DISSEMINATION OF DRYLAND CONSERVATION TECHNOLOGY BY OPINION LEADERS IN BANTUL DISTRICT, YOGYAKARTA) - Adi, R Kunto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
The research aims to know the dissemination of conservation technology by opinion leaders, extension agents, and the media. Primary data collecting was done through interviews of 60 samples. Data analysis was conducted with ANOVA. The research reveals that dissemination of conservation technology at higher levels and the role of opinion leaders are more influential to the diffusion level of conservation technology than those of extension agents and the media.